2011 International Reliability Physics Symposium 2011
DOI: 10.1109/irps.2011.5784609
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of the recoverable component of the SiON, HfSiON and HfO<inf>2</inf> P-MOSFETs under dynamic NBTI

Abstract: The evolution of the recoverable (R) component of negative-bias temperature instability (NBTI) is examined, as a function of the number of stress and relaxation cycles, for the SiON, HfSiON, and HfO 2 p-MOSFETs. At typical NBTI oxide fields (~7 MV/cm), a steady and substantial decrease of the R component in the case of the HfO 2 p-MOSFET is observed, while the R component of the SiON and HfSiON p-MOSFETs are found to remain constant. A decrease in the R component of the SiON and HfSiON p-MOSFETs is observed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
7
17
0
Order By: Relevance
“…The results confirm our earlier inference of transient to permanent hole trap transformation, derived from the decreasing recovery per cycle of a large area device subjected to NBTI stress/relaxation cycling [2]- [6]. While the nature of such defects remains elusive, the study clearly shows that trap parameters such as the emission time constant are not time-invariant but evolve continuously during stress.…”
Section: #4supporting
confidence: 88%
See 1 more Smart Citation
“…The results confirm our earlier inference of transient to permanent hole trap transformation, derived from the decreasing recovery per cycle of a large area device subjected to NBTI stress/relaxation cycling [2]- [6]. While the nature of such defects remains elusive, the study clearly shows that trap parameters such as the emission time constant are not time-invariant but evolve continuously during stress.…”
Section: #4supporting
confidence: 88%
“…One of the major challenges in modeling NBTI lies in its transient nature, which has been recently shown to be mainly linked to the capture and emission of holes by switching oxide traps (SOTs) under pulsed gate stressing [2]. Our recent studies [3]- [6] have suggested that a portion of the SOTs may be progressively transformed into a more permanent form. These studies were made on large area devices and the conclusion was drawn based on the decrease of the recoverable component of NBTI as dynamic stressing progresses.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a decrease in R is apparent at a higher temperature (100 °C). This decrease means that a fraction of the trapped holes is rendered more permanent as the DNBTI experiment progresses [9], [10]. This is evident from Fig.…”
Section: Introductionmentioning
confidence: 67%
“…The optional bake steps, typically performed for 1h at 350 • C, are motivated by the observation that in large-area devices such a bake restores the initial state prior to degradation [15,16]. Furthermore, it has been observed that upon repeated stress/recovery cycling the amount of recoverable defects typically decreases with time [6,7,9,17,18], which is the macroscopic (large area) equivalent of defect volatility. In large-area devices it has been found that baking can also reverse this net loss of defects [12].…”
Section: Methodsmentioning
confidence: 99%
“…This is because charge traps responsible for RTN also form a significant contribution to BTI [4][5][6][7]. In particular, it has been shown by several groups that upon repeating charging and discharging cycles, the average number of active oxide defects in largearea devices can decrease [6][7][8][9], particularly under harsher stress conditions. However, the detailed dependencies and the nature of the chemical reactions leading to this defect volatility have not yet been explored.…”
Section: Introductionmentioning
confidence: 99%